Žižek's jokes : (did you hear the one about Hegel and negation?) - Žižek, Slavoj (MIT Press, 2013)
Zizek as comedian: jokes in the service of philosophy."A serious and good philosophical work could be written consisting entirely of jokes."--Ludwig WittgensteinThe good news is that this book offers an entertaining but enlightening compilation of Zizekisms. Unlike any other book by Slavoj Zizek, this compact arrangement of jokes culled from his writings provides an index to certain philosophical, political, and sexual themes that preoccupy him. Zizek's Jokes contains the set-ups and punch lines--as well as the offenses and insults--that Zizek is famous for, all in less than 200 pages. So what's the bad news? There is no bad news. There's just the inimitable Slavoj Zizek, disguised as an impossibly erudite, politically incorrect uncle, beginning a sentence, "There is an old Jewish joke, loved by Derrida ..." For Zizek, jokes are amusing stories that offer a shortcut to philosophical insight. He illustrates the logic of the Hegelian triad, for example, with three variations of the "Not tonight, dear, I have a headache" classic: first the wife claims a migraine; then the husband does; then the wife exclaims, "Darling, I have a terrible migraine, so let's have some sex to refresh me!" A punch line about a beer bottle provides a Lacanian lesson about one signifier. And a "truly obscene" version of the famous "aristocrats" joke has the family offering a short course in Hegelian thought rather than a display of unspeakables. Zizek's Jokes contains every joke cited, paraphrased, or narrated in Zizek's work in English (including some in unpublished manuscripts), including different versions of the same joke that make different points in different contexts. The larger point being that comedy is central to Zizek's seriousness